Physically reasonable time sampling in mathematical models of generators of regular and chaotic oscillations - V.V. Zaitsev (Физика волновых процессов и радиотехнические системы, 2019)
The issue of transition to discrete time in mathematical models of nonlinear dynamic systems oscillating in continuous time is considered. On the basis of the examples of the Dmitriev Kislov and van der Pol generators, the approach based on maintaining in the process of time sampling the impulse response of the linear oscillatory circuit included in the generator is described. This physically reasonable sampling allows models of non-linear dynamics to be formulated in discrete time, adequately reproducing the characteristics of analog prototypes, which is not always possible with a widely used combination of explicit and implicit Euler methods.